Prevention and Eradication of Money Laundering Crime in Banking - Syahda, Illa Fatika; Putra, Rizki Dwi; Syafa, Tazkia Suhaila; Sinlae, Ester Stevany Putri (Veteran Law Review, 2024)
Preventing and combating money laundering (AML) in the banking sector has become an important focus for governments and financial regulators in many countries. Money laundering has important implications for economic stability and the integrity of the global financial system. This article provides an overview of ML prevention and elimination strategies implemented in the banking sector. The emphasis is on existing policies, regulations and practices designed to identify, monitor and prevent the flow of illicit funds through the banking system. In addition, an effective control framework and cooperation between the government, financial institutions and the private sector are discussed. While the challenges of combating money laundering continue to increase, these joint actions demonstrate a commitment to reducing financial criminal risk and strengthening the integrity of the banking sector. In addition, the use of technology such as data analysis and artificial intelligence is also becoming an important tool for early detection and monitoring of suspicious transactions. Therefore, close cooperation between banks, regulators and law enforcement is essential to create a transparent banking system free from financial crime.